2011
DOI: 10.4103/0019-5359.104788
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological efficacy of argemone mexicana plant extract, against cysteamine-induced duodenal ulceration in rats

Abstract: The plant A. mexicana Linn. Increased healing of gastric ulceration and prevented the development of experimentally induced duodenal ulceration in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 5 publications
1
9
0
1
Order By: Relevance
“…Surprisingly, the activity of the extract was higher at the dose of 250 mg/kg when compared with the dose of 500 mg/kg. This agrees with the finding of Das et al [29] , who reported better efficacy of extract of Argemone mexicana at lower dose than at higher dose. This effect may perhaps be attributed to the antioxidant action of the extract.…”
Section: Discussionsupporting
confidence: 93%
“…Surprisingly, the activity of the extract was higher at the dose of 250 mg/kg when compared with the dose of 500 mg/kg. This agrees with the finding of Das et al [29] , who reported better efficacy of extract of Argemone mexicana at lower dose than at higher dose. This effect may perhaps be attributed to the antioxidant action of the extract.…”
Section: Discussionsupporting
confidence: 93%
“…Earlier studies have documented that A. mexicana is likely to contain benzylisoquinoline alkaloids such as benzophenanthridines, sanguarine, rotoberberines and protopines, protomexicine, mexitin dehydrocorydalmine, jatrorrhizine, columbamine, dl-tetrahydrocoptisine and dihydrocoptisine [21,22,23,24,25,26]. In an independent study on rodents [22], A. mexicana extracts were found to be effective in curing ulcers induced with cystamine.…”
Section: Discussionmentioning
confidence: 99%
“…In an independent study on rodents [22], A. mexicana extracts were found to be effective in curing ulcers induced with cystamine. In their work, Zhou et al, [27] used reseveratrol, whereas Mohan et al [28] used ethylgallate to study anti-proliferative effects on human oral squamous immortalized cell line KB.…”
Section: Discussionmentioning
confidence: 99%
“…Argemone mexicana L. is a plant that contains numerous alkaloids and is widely used in traditional medicine. A study carried out to assess the effects of methanol and aqueous extracts from this plant (500–3000 mg/kg), in Wistar rats with duodenal ulceration, concluded that both extracts produced significant activity in cysteamine-induced duodenal ulceration [ 93 ].…”
Section: Plant Products and Phytochemicals As Antiulcerogenic And mentioning
confidence: 99%